الأهمية النسبية لمحاور التنافسية ودورها في النمو الاقتصادي في سورية - العلي ابراهيم; العشعوش أيمن; أحمد أحمد ديب (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يُعدُّ مفهوم التنافسية مفهومًا اقتصادياً حديثاً يتصف بالديناميكية، ويتألف من ثلاثة محاور هي: المتطلبات الأساسية، ومعززات الكفاءة، وعوامل تطور الإبداع. ويجب الاهتمام بموضوع التنافسية والاستفادة من مفهومها حتى تتمكن من تحقيق التطور والنمو الاقتصادي، وتحسين مستوى معيشة المواطنين. لقد قمنا في هذا البحث بدراسة العلاقة بين نصيب الفرد من الناتج المحلي الإجمالي كمعيار للنمو الاقتصادي من جهة، ومؤشر التنافسية من جهة أخرى، وتحديد الأولويات التي تشكلها محاور التنافسية في حساب قيمة هذا المؤشر بغاية الوصول إلى نماذج قياسية تلعب دورها في تحديد العلاقات والتنبؤ بالقيم المستقبلية، وتحديد الاستراتيجية المناسبة للنمو الاقتصادي. وحصلنا على أن المتطلبات الأساسية تلعب الدور الأكبر في تخطيط النمو الاقتصادي حيث تشكل الأولوية الأولى في تحديد قيمة مؤشر التنافسية بأهمية نسبية 45%، تليها معززات الكفاءة كأولوية ثانية أهميتها النسبية 34%، بينما تبين لنا أن عوامل تطور الإبداع التي تشكل الأولوية الثالثة تلعب دورًا طفيفًا في تحقيق النمو الاقتصادي حيث تبلغ أهميتها النسبية 21% فقط. ومن هذه النتائج نستخلص أن مؤشر التنافسية يعتمد على المحاور الخدمية والتجارية ولا يعطي تطور الإبداع الأهمية التي يستحقها في تحقيق النمو الاقتصادي والتقدم الحضاري. The concept of competitiveness is a new economic concept characterized by dynamism and consists of three axes, which are basic requirements, efficiency enhancers and creativity development factors. Therefore, attention must be paid to competitiveness and benefit should be obtained from its concept to achieve economic development, growth and improving people’s living standard. In this research we studied the relationship between per capita GDP as a touchstone of economic growth on the one hand, and competitiveness index on the other. We also determined priorities posed by competitive axes in calculating the value of this index to get standard models that play a role in determining relations and predicting future values, and determining the appropriate strategy for economic growth. We concluded that the basic prerequisites play the largest role in the planning of economic growth (45%), followed by boosters (34%), and we discovered that creativity development factors play a trivial role in economic growth (21%). These results indicate that the competitive index depends on the service and commercial hubs and creativity development is not given the attention it deserves as it has an essential role in the economic growth and cultural progress.